On The Aerodynamic Damping Mechanism Of Vehicle Pitching Stability Using Large Eddy Simulation - Cheng, See Yuan; Tsubokura, Makoto; Nakashima, Takuji; Nouzawa, Takahide; Okada, Yoshihiro (2010)
Large eddy simulation was conducted to investigate the pitching stability characteristic of notchback-type vehicle. In this paper, two simplified vehicle models represent the notchback of different pitching stability characteristics were used. Numerical method adopted was validated by comparing the simulation result with wind tunnel data. To probe the dynamic response of the models, forced-sinusoidal-pitching oscillation is imposed and the resulting pitch moment is phase averaged, and decomposed into the stationary, quasi-stationary, and dynamic components for assessment. Vehicle model of higher aerodynamic damping is found to exhibit two-dimensional flow structure above the central region of its trunk deck, whereas vehicle model of lower aerodynamic damping is associated with strong cross flow and upwash circulatory flow structure. The outcome of this work demonstrates how unsteady aerodynamics can be exploited for the control of vehicle’s straight ahead stability.